Autologous Protein Solution Effect on Chondrogenic Differentiation of Mesenchymal Stem Cells from Adipose Tissue and Bone Marrow in an Osteoarthritic Environment. (December 2021) - Pagani, Stefania; Veronesi, Francesca; Giavaresi, Gianluca; Filardo, Giuseppe; Papio, Tiziana; Romandini, Iacopo; Fini, Milena
Objective: Osteoarthritis (OA) is an inflammatory and degenerative disease, and the numerous treatments currently used are not fully effective. Mesenchymal stem cells (MSCs) and platelet-rich plasma (PRP) are proposed for OA treatment as biologic therapies. The aim of the study was to observe the role of autologous protein solution (APS), a type of PRP, on chondrogenic differentiation of 2 types of MSCs, from bone marrow (BMSCs) and adipose tissue (ADSCs), in an in vitro osteoarthritic microenvironment. Design: Inflammatory culture conditions, mimicking OA, were obtained by adding interleukin-1β (IL-1β) and tumor necrosis factor α (TNFα), or synovial fluid from patient osteoarthritic knees (OSF), to the culture medium. MSCs were then treated with APS. Results: After 1 month of culture, both cell types formed mature micromasses, partially altered in the presence of IL-1β and TNFα but quite preserved with OSF. Inflammatory conditions hindered differentiation in terms of gene expression, not counterbalanced by APS. APS triggered type I collagen deposition and above all contributed to decrease the expression of metalloproteinases in the most aggressive conditions (IL-1β and TNFα in the culture medium). ADSCs originated micromasses more mature and less prone toward osteogenic lineage than BMSCs, thus showing to better adapt in an aggressive environment than BMSC. Conclusions: APS seems to act better on inflammation front and, between cell types, ADSCs respond better to the inflammatory microenvironment of OA and to the treatment with APS than BMSCs.